2020
DOI: 10.1016/j.arrct.2020.100071
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Modified Heckmatt Scale in Evaluating Muscle Changes With Ultrasound in Spasticity

Abstract: Objectives To determine the reliability and validity of the Modified Heckmatt scale in assessing muscle echotexture in spasticity. Design Prospective, observational, 2-center study. Two residents and 2 ultrasound experienced staff physicians each rated 100 ultrasound images that were also analyzed using quantitative gray-scale. Setting Academic ambulatory spasticity clinic. Participants Participants (N=50) included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 24 publications
2
33
0
1
Order By: Relevance
“…Adequate field of view and depth are necessary to recognize bony landmarks. Patients who have had long-standing BoNT injections and increased spasticity often have increased muscle fibrosis leading to loss of muscle fascial planes used to delineate muscles from each other [ 12 , 36 , 37 ]. In these cases, it may be necessary to use bony landmarks such as the tibia and the interosseous membrane for identifying tibialis posterior or the radius and ulna for flexor compartment muscles as a strategy to identify fibrosed muscles under ultrasound ( Figure 5 ) and use of the Modified Heckmatt Scale for identification of muscle fibrosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adequate field of view and depth are necessary to recognize bony landmarks. Patients who have had long-standing BoNT injections and increased spasticity often have increased muscle fibrosis leading to loss of muscle fascial planes used to delineate muscles from each other [ 12 , 36 , 37 ]. In these cases, it may be necessary to use bony landmarks such as the tibia and the interosseous membrane for identifying tibialis posterior or the radius and ulna for flexor compartment muscles as a strategy to identify fibrosed muscles under ultrasound ( Figure 5 ) and use of the Modified Heckmatt Scale for identification of muscle fibrosis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, proper use of gain and ultrasound probe selection can help determine the level of muscle echointensity (spastic muscles are more hyperechoic secondary to muscle atrophy, increased fat infiltration and fibrosis), which can be visually assessed by the Modified Heckmatt scale for spasticity [ 36 ]. Picelli et al demonstrated that outcomes to BoNT may be affected if a spastic muscle is more fibrotic [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity is around 71%-76%, depending on the subject and the observer's experience [53]. A promising study performed in the USA of patients with muscle spasticity, in which they compared the Heckmatt scale with quantitative gray-scale analysis, concluded that there is a good correlation between both methods, indicating a high validity [61]. Therefore, for the near future it might be feasible to investigate the inter-rater reliability for using the Heckmatt scale in order to implement it in practice.…”
Section: Muscle Denervation In Shoulder Disordersmentioning
confidence: 99%